Bruce Bronzan Press Conference re Candidate for 31st Assembly District at Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Peggy Bronzan, Bruce Bronzan speaking at lectern; Linda Bronzan holding Chloe Bronzan Portable high end cassette tape recorder on table